Dynapaenia and sarcopaenia in chronic haemodialysis patients: do muscle weakness and atrophy similarly influence poor outcome?. Issue 10 (11th December 2020) - Souweine, Jean-Sébastien; Pasquier, Grégoire; Kuster, Nils; Rodriguez, Annie; Patrier, Laure; Morena, Marion; Badia, Eric; Raynaud, Fabrice; Chalabi, Lotfi; Raynal, Nathalie; Ohresser, Isabelle; Hayot, Maurice; et al.
Abstract: Background: Sarcopaenia, defined as a decline in both muscle mass and function, has been recognized as a major determinant of poor outcome in haemodialysis (HD) patients. It is generally assumed that sarcopaenia is driven by muscle atrophy related to protein-energy wasting. However, dynapaenia, defined as weakness without atrophy, has been characterized by a different disease phenotype from sarcopaenia. The aim of this study was to compare the characteristics and prognosis of sarcopaenic and dynapaenic patients among a prospective cohort of chronic HD (CHD) patients. Methods: Two hundred and thirty-two CHD patients were enrolled from January to July 2016 and then followed prospectively until December 2018. At inclusion, weakness and atrophy were, respectively, evaluated by maximal voluntary force (MVF) and creatinine index (CI). Sarcopaenia was defined as the association of weakness and atrophy (MVF and CI below the median) while dynapaenia was defined as weakness not related to atrophy (MVF below the median, and CI above the median). Results: From a total of 187 prevalent CHD patients [65% of men, age 65.3 (49.7–82.0) years], 44 died during the follow-up period of 23.7 (12.4–34.9) months. Sarcopaenia and dynapaenia were observed in 33.7 and 16% of the patients, respectively. Compared with patients with sarcopaenia, patients with dynapaenia were younger and with a lower Charlson score. In contrast, mortality rate was similar in both groups (38 and 27%, respectively). After adjustment for age, sex, lean tissue index, serum albumin, high-sensitivity C-reactive protein (hs-CRP), haemoglobin (Hb), normalized protein catabolic rate (nPCR), dialysis vintage and Charlson score, only patients with dynapaenia were at increased risk of death [hazard ratio (HR) = 2.99, confidence interval 1.18–7.61; P = 0.02]. Conclusions: Screening for muscle functionality is highly warranted to identify patients with muscle functional impairment without muscle atrophy. In contrast to sarcopaenia, dynapaenia should appear as a phenotype induced by uraemic milieu, characterized by young patients with low Charlson score and poor prognosis outcome independently of serum albumin, hs-CRP, Hb, nPCR and dialysis vintage. Graphical Abstract: